Evidence for prodromal changes in neuronal excitability and neuroinflammation in the hippocampus in young alpha-synuclein (A30P) transgenic mice - Al-Musawi, Ibtisam; Dennis, Bethany H.; Clowry, Gavin J.; LeBeau, Fiona E. N. (Frontiers in Dementia, 2024)
Neuronal hyperexcitability and neuroinflammation are thought to occur at early stages in a range of neurodegenerative diseases. Neuroinflammation, notably activation of microglia, has been identified as a potential prodromal marker of dementia with Lewy bodies (DLB).Using a transgenic mouse model of DLB that over-expresses human mutant (A30P) alphasynuclein (h-syn) we have investigated whether early neuroinflammation is evident in the hippocampus in young pre-symptomatic animals. Previous studies have shown early hyperexcitability in the hippocampal CA3 region in male A30P mice at 2-4 months of age, therefore, in the current study we have immunostained this region for markers of neuronal activity (c-Fos), reactive astrocytes (glial fibrillary acidic protein, GFAP), microglia (ionizing calcium binding adapter protein 1, Iba-1) and reactive microglia (inducible nitric oxide synthase, iNOS). We found an interesting biphasic change in the expression of c-Fos in A30P mice with high expression at 1 month, consistent with early onset of hyperexcitability, but lower expression from 2-4 months in male A30P mice compared to wild-type (WT) controls, possibly indicating chronic hyperexcitability. Neuroinflammation was indicated by significant increases in the % area of GFAP and the number of Iba-1+ cells that expressed iNOS immunoreactivity in the CA3 region in 2-4 months A30P male mice compared to WT controls. A similar increase in % area of GFAP was observed in female A30P mice, however, the Iba-1 count was not different between female WT and A30P mice. In WT mice aged 2-4 months only 4.6% of Iba-1+ cells co-expressed iNOS. In contrast, in age matched A30P mice 87% of cells coexpressed Iba-1 and iNOS. Although there was no difference in GFAP immunoreactivity at 1 month, Iba-1/iNOS co-expression was also increased in a cohort of 1 month old A30P mice.Abnormal h-syn expression in A30P mice caused early changes in network excitability, as indicated by c-Fos expression, and neuroinflammation which might contribute to disease progression.